Soft switched SVPWM controlled PRDCL inverter - Akin, Burak; Sarul, Mustafa Hadi (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
In this study, soft switched space vector PWM controlled parallel-resonant DC link (PRDCL) inverter is proposed for fuel cells (FC) applications. The proposed circuit is applied to an induction motor to evaluate the converter system. Application and simulation results are compared and the results are both compatible. It is observed that all the semiconductor switches in the circuit are turned on and off nearly zero voltage switching (ZVS) or zero current switching (ZCS). There are no additional extra voltage stress on the main switch. The semiconductor switching losses are obtained with considering the module temperature variation. The proposed soft switched SVPWM controlled PRDCL inverter has 95.3% efficiency at full load. (C) 2017 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Fuel cell; Parallel resonance-DC link inverter; Soft switching; Space vector; ZCS; ZVS; DC-LINK INVERTER; MOTOR DRIVE SYSTEM; Chemistry; Electrochemistry; Energy & Fuels